Examining the Association of Hemodialysis Adherence with Blood Pressure in Chronic Renal Failure - Yulianti, Yeni; Nallappan, Devi (International Journal of Nursing Information, 2023)
Medication adherence is important for people with chronic renal failure (CRF) undergoing hemodialysis. Lowering blood pressure can reduce symptoms and improve the long-term health of hemodialysis patients.  Hypertension is more prevalent and more complex to control in patients with chronic kidney disease and can also be a cause or result of the condition. This study aimed to investigate the association between blood pressure and hemodialysis therapy adherence in patients with renal failure. This study employed a descriptive correlation method to examine patients with CRF who are currently undergoing hemodialysis therapy and have a history of hypertension. In this study, 31 respondents were selected using purposive sampling. Data on medication adherence were collected by questionnaire, while blood pressure readings were used to examine the prevalence of hypertension. The research location is the government hospital in Sukabumi, Indonesia. A chi-square statistical test was used for data analysis. The result showed a relationship between hemodialysis therapy compliance and the incidence of hypertension in patients with chronic renal failure who are undergoing hemodialysis therapy. In patients with chronic renal failure receiving hemodialysis, there is a significant positive correlation between blood pressure and treatment adherence. Research contributes that adherence to the prescribed hemodialysis regimen may play a crucial role in the management and prevention of hypertension in this patient population.